Secondary battery and electric device
Patent Information
- Application Number
- CN202380060756.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2025-03-28
AI Technical Summary
While increasing the energy density of existing secondary batteries, the rate performance is affected, especially due to the reduced compaction density and increased resistance of the negative electrode film layer caused by larger silicon-carbon composite particles.
By introducing a second particle size material into the negative electrode active material, the average particle size relationship between the first particle size material and the second particle size material is controlled (D2/D1≤0.6) to improve the compaction density of the negative electrode film layer and the inter-particle contact area, reduce resistance, and optimize the content and structure of silicon-carbon composite materials.
It achieves a secondary battery with both high-quality energy density and high-rate performance, significantly improving the volumetric energy density and overall performance of the battery.
Smart Images

Figure CN119731798A_ABST
Abstract
Description
Secondary battery and power-consuming device Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] In recent years, as secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, the market's performance requirements for secondary batteries have become increasingly higher.
[0003] At present, with the increase in the battery life or mileage of various electrical devices, the energy density requirements for secondary batteries are also getting higher and higher. In order to obtain higher energy density, silicon-based materials are usually used in the negative electrode active materials, but the electrochemical performance of the battery will be affected.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its object is to provide a secondary battery that has high energy density and good rate performance.
[0006] A first aspect of the present application provides a secondary battery, which includes a negative electrode plate, the negative electrode plate includes a negative electrode active material, the negative electrode active material includes a first particle size material and a second particle size material, the average particle size D1 of the first particle size material and the average particle size D2 of the second particle size material satisfy: D2 / D1≤0.6, and the first particle size material includes a silicon-carbon composite material, the silicon-carbon composite material includes carbon matrix particles and a silicon-based material arranged inside the carbon matrix particles.
[0007] The carbon matrix particles of the present application can provide more space for the deposition of silicon-based materials, thereby accommodating more silicon-based materials. Since the specific capacity of silicon-based materials is relatively high, the silicon-carbon composite material of the present application can increase the capacity of the negative electrode active material, thereby improving the mass energy density of the secondary battery. However, due to the large size of the silicon-carbon composite material particles with an internal void structure, the compaction density of the negative electrode film layer is reduced, thereby reducing the energy density of the secondary battery. At the same time, the large number of pores between the large particles will agglomerate a large amount of binder and conductive agent, thereby affecting the electrical contact between the particles, causing the resistance of the negative electrode plate to increase, further affecting the rate performance of the secondary battery. The present application introduces a second particle size material, and further controls the average particle size relationship between the first particle size material and the second particle size material to meet D2 / D1≤0.6. When the above relationship is met, the second particle size material can be filled into the pores of the first particle size material to the maximum extent, effectively increasing the compaction density of the negative electrode film layer, thereby increasing the energy density of the secondary battery. At the same time, the increase in contact area between the particles also reduces the resistance of the negative electrode plate and improves the rate performance of the secondary battery.
[0008] In any embodiment, D2 / D1≤0.6-0.155lnα, wherein α is the mass ratio of the first particle size material to the second particle size material, and α≥1.
[0009] In any embodiment, 3≤α≤9.
[0010] Increasing the mass content of silicon-carbon composite materials can improve the mass energy density of secondary batteries. However, excessive amounts of large silicon-carbon composite materials can reduce the compaction density of the negative electrode film layer, decrease the contact area between particles, increase the resistance of the negative electrode sheet, and reduce the rate performance of the secondary battery. The applicant unexpectedly discovered that when the average particle size and mass gradation design relationship of the first and second particle size materials in the negative electrode active material satisfies the above relationship, the secondary battery achieves both high compaction density and high mass energy density, thereby achieving higher volumetric energy density, lower resistance, and higher rate performance.
[0011] In any embodiment, 5 μm ≤ D1 ≤ 20 μm, optionally 5 μm ≤ D1 ≤ 15 μm.
[0012] When the particle size of the first particle size material is too large, the resistance to charge transfer increases, the rate performance decreases, and the compaction density is also affected. When the particle size of the first particle size material is too small, the amount of silicon-based material contained in the silicon-carbon composite material decreases, thereby reducing the mass energy density of the secondary battery and also reducing the compaction density. Controlling the particle size of the first particle size material within an appropriate range is beneficial to increasing the compaction density, reducing the resistance, and improving the rate performance of the secondary battery. It can also increase the mass energy density and volume energy density of the secondary battery.
[0013] In any embodiment, 1 μm≤D2≤10 μm, optionally 2 μm≤D2≤5 μm.
[0014] When the particle size of the second particle material is too large, the charge transfer resistance increases, the rate performance decreases, and the compaction density is also affected. When the particle size of the second particle material is too small, the initial efficiency and capacity are low. Controlling the particle size of the second particle material within an appropriate range helps to increase the compaction density, reduce the resistance, and improve the rate performance of the secondary battery. It can also increase the mass energy density and volume energy density of the secondary battery.
[0015] In any embodiment, the particle size distribution of the negative electrode active material satisfies: 0.9≤(Dv90-Dv10) / Dv50≤2.
[0016] In any embodiment, the particle size distribution of the first particle size material satisfies: (Dv190-Dv110) / Dv150≤2.0, which can be optionally 1.2≤(Dv190-Dv110) / Dv150≤2.0; and / or the particle size distribution of the second particle size material satisfies: (Dv290-Dv210) / Dv250≤1.6, which can be optionally 0.9≤(Dv290-Dv210) / Dv250≤1.3.
[0017] When the particle size distribution of the negative electrode active material meets the above range, the overall particle size of the negative electrode active material is relatively moderate and the particle size distribution is uniform, which is beneficial to improving the uniformity of the overall performance of the negative electrode active material.
[0018] In any embodiment, the average aspect ratio R1 of the first particle size material is 1.2-2.5; and / or the average aspect ratio R2 of the second particle size material is 1.2-3.0.
[0019] By controlling the average aspect ratio of the first particle size material and / or the second particle size material within a suitable range, the particle shapes of the first particle size material and the second particle size material can be controlled to be more regular, thereby increasing the compaction density of the negative electrode film layer.
[0020] In any embodiment, the carbon matrix particles include a three-dimensional network cross-linked pore structure, and at least a portion of the silicon-based material is disposed in the three-dimensional network cross-linked pore structure.
[0021] The three-dimensional network cross-linked pore structure can provide more space for silicon-based materials, can accommodate more silicon-based materials, and improve the mass energy density of secondary batteries.
[0022] In any embodiment, the carbon content in the silicon-carbon composite material has a decreasing trend from the geometric center of the silicon-carbon composite material to the outer surface; and / or, the silicon content in the silicon-carbon composite material has an increasing trend from the geometric center of the silicon-carbon composite material to the outer surface.
[0023] In any embodiment, based on the total mass of the silicon-carbon composite material, the silicon element content is greater than or equal to 20%, and can be optionally 20%-60%; and / or, based on the total mass of the silicon-carbon composite material, the carbon element content is greater than or equal to 40%, and can be optionally 40%-70%; based on the total mass of the silicon-carbon composite material, the oxygen element content is less than or equal to 10%, and can be optionally 1%-5%.
[0024] When the content of the silicon-based material attached to the carbon-based particles of the present application meets the above range, the relatively high content of the silicon-based material can significantly increase the capacity of the secondary battery, thereby increasing its mass energy density. A moderate content of the carbon-based particles can improve the conductivity of the negative electrode active material, thereby reducing the resistance of the negative electrode sheet.
[0025] In any embodiment, the mass content of the silicon-carbon composite material in the negative electrode active material is greater than or equal to 50%, and can be optionally greater than or equal to 70%.
[0026] When the content of silicon-carbon composite material increases, it is beneficial to improve the energy density of secondary batteries.
[0027] In any embodiment, the second particle size material comprises a carbon-based material; optionally, the carbon-based material comprises one or more of graphite, hard carbon, soft carbon, porous carbon or activated carbon.
[0028] When the second particle size material includes a carbon-based material, the ability of the negative electrode plate to transport ions can be improved, and the rate performance of the secondary battery is effectively improved.
[0029] In any embodiment, the negative electrode plate includes a negative electrode film layer, and the compaction density of the negative electrode film layer is 1.2 g / cm 3 -1.6g / cm 3 Optionally, the compaction density of the negative electrode film is 1.3 g / cm 3 -1.6g / cm3 .
[0030] When the compaction density of the negative electrode film layer is increased, the volume energy density of the secondary battery can be significantly improved.
[0031] In any embodiment, the mass energy density of the secondary battery is 380Wh / kg-460Wh / kg, optionally, the mass energy density of the secondary battery is 400Wh / kg-460Wh / kg; and / or the volume energy density of the secondary battery is 650Wh / L-1000Wh / L, optionally, the volume energy density of the secondary battery is 700Wh / L-1000Wh / L.
[0032] A second aspect of the present application provides an electrical device, which includes the secondary battery described in the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] FIG1 is a schematic diagram of a negative electrode sheet according to an embodiment of the present application;
[0034] FIG2 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0035] FIG3 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG2 ;
[0036] FIG4 is a schematic diagram of a battery module according to an embodiment of the present application;
[0037] FIG5 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0038] FIG6 is an exploded view of the battery pack shown in FIG5 according to an embodiment of the present application;
[0039] FIG. 7 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0040] Explanation of the reference numerals: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 cover plate; 6 negative electrode sheet; 61 first particle size material; 62 second particle size material; 63 negative electrode current collector. DETAILED DESCRIPTION
[0041] Below, the embodiments of the negative electrode sheet, secondary battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0042] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0044] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0045] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0046] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0047] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0048] Silicon is widely used as a negative electrode active material to increase the energy density of secondary batteries due to its high capacity. However, the high-silicon silicon-carbon composite material has large particles, which will reduce the compaction density of the negative electrode film layer, thereby greatly reducing the volume energy density of the secondary battery. In order to solve the above problems, the applicant has discovered through continuous research that by introducing a second particle size material into the negative electrode active material, especially controlling the relationship between the average particle size of the second particle size material and the silicon-carbon composite material, the compaction density of the negative electrode film layer can be increased, thereby increasing the volume energy density of the secondary battery. At the same time, it can also reduce the electrode sheet resistance and improve the rate performance of the secondary battery.
[0049] [Secondary battery]
[0050] Based on this, the present application proposes a secondary battery, which includes a negative electrode plate, the negative electrode plate includes a negative electrode active material, the negative electrode active material includes a first particle size material and a second particle size material, the average particle size D1 of the first particle size material and the average particle size D2 of the second particle size material satisfy: D2 / D1≤0.6, and the first particle size material includes a silicon-carbon composite material, the silicon-carbon composite material includes carbon matrix particles and a silicon-based material arranged inside the carbon matrix particles.
[0051] In some embodiments, the average particle size D1 of the first particle size material and the average particle size D2 of the second particle size material satisfy: D2 / D1≤0.5, D2 / D1≤0.4, D2 / D1≤0.3, D2 / D1≤0.25, D2 / D1≤0.23, D2 / D1≤0.2, D2 / D1≤0.15, D2 / D1≤0.14, D2≤0.13, or D2 / D1 can also be a value within the range formed by any two of the above points.
[0052] 1 , the negative electrode sheet 6 includes a first-size particle material 61, a second-size particle material 62, and a negative electrode current collector 63. The second-size particle material is filled in the pores of the first-size particle material.
[0053] The average particle size of the first particle size material and the second particle size material has a well-known meaning in the art and can be measured using methods and equipment known in the art. As an example, the following steps can be used: cut the negative electrode plate into a sample of a certain size to be tested (for example, 6mm×6mm), observe the surface active particles of the plate by scanning electron microscopy, and perform statistical analysis of the material particle size using Image J software. A bimodal normal distribution curve is used for fitting, and the large particle size and small particle size corresponding to the two peaks are used as D1 and D2, respectively. The type of large and small particle size materials can be further determined by analyzing the material elements using an energy spectrometer.
[0054] In some embodiments, the carbon matrix particles include a skeleton structure or a porous skeleton structure, at least a portion of the silicon-based material is attached to the pores of the carbon skeleton, and the silicon-based material can fill all or part of the pores of the carbon skeleton. The pores therein refer to structures that are recessed relative to the outer surface of the negative electrode active material, or through-holes that penetrate the negative electrode active material. The composition of the pore structure includes pore size, pore length, pore size distribution, etc. The pores of the carbon matrix particles include at least one of micropores, mesopores, and macropores. Generally, micropores refer to pores with a diameter of less than about 2 nanometers. Mesopores refer to pores with a diameter of about 2 nanometers to about 5 nanometers. Macropores refer to pores with a diameter greater than 50 nanometers.
[0055] The pore structure characteristics of the silicon-carbon composite material in the negative electrode plate can be observed using methods and equipment known in the art. For example, a negative electrode plate containing a silicon-carbon composite material can be taken and observed under a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be referred to: take the negative electrode plate, cut the negative electrode plate into a sample to be tested of a certain size (for example, 6 mm × 6 mm), clamp the sample to be tested with two conductive and thermally conductive thin sheets (such as copper foil), stick the sample to be tested and the copper foil with glue (such as double-sided tape), press it with a flat iron block of a certain mass (such as 400 g) for a certain time (such as 1 hour), trim the edges with scissors, and stick it on a sample table with conductive glue. Then, the sample stage is placed on the sample holder and fixed. The argon ion cross-section polisher (such as IB-19500CP) is turned on and vacuum is applied (for example, to 10Pa-4Pa). The argon flow rate (for example, 0.15MPa), voltage (for example, 8KV), and polishing time (for example, 2 hours) are set. The sample stage is adjusted to the rocking mode and polishing is started. After polishing is completed, a scanning electron microscope (such as ZEISS Sigma 300) is used to obtain an ion-polished cross-sectional morphology image of the sample to be tested.
[0056] In some embodiments, the particle size of the silicon-based material is at the nanometer level. When the silicon-based material is deposited, the nano-silicon-based material is more easily and evenly attached to the interior of the carbon matrix particles.
[0057] The resistance of the negative electrode sheet can be measured using methods and equipment known in the art. For example, it can be measured using a resistance meter. As an example, you can refer to the following steps: cut small discs of a certain diameter (for example, 20 mm) on the left, middle, and right sides of the negative electrode sheet. Turn on the indicator light of the sheet resistance meter, place it in the appropriate position of the "probe" of the film resistance meter, wait for the display to stabilize, and read the data. Test two positions of each small disc, and finally calculate the average of the six measurement data, which is the sheet resistance of the electrode sheet.
[0058] The carbon-based particles of the present application can provide more space for the deposition of silicon-based materials, thereby accommodating more silicon-based materials. Due to the relatively high specific capacity of silicon-based materials, the silicon-carbon composite material of the present application can increase the capacity of the negative electrode active material, thereby improving the mass energy density of the secondary battery. However, due to the large size of the silicon-carbon composite particles containing an internal void structure, the compaction density of the negative electrode film layer is reduced, resulting in a decrease in the energy density of the secondary battery. At the same time, the large number of pores between the large particles will agglomerate a large amount of binder and conductive agent, thereby affecting the electrical contact between the material particles, causing the resistance of the negative electrode plate to increase, further affecting the rate performance of the secondary battery. The present application introduces a second particle size material and further controls the average particle size relationship between the first particle size material and the second particle size material to satisfy D2 / D1≤0.6. When the above relationship is met, the second particle size material can be filled into the pores of the first particle size material to the maximum extent, effectively increasing the compaction density of the negative electrode film layer and the mass energy density of the secondary battery, thereby improving the energy density of the secondary battery. At the same time, the increased contact area between the particles also reduces the resistance of the negative electrode plate, thereby improving the rate performance of the secondary battery.
[0059] In some embodiments, D2 / D1≤0.6-0.155lnα, wherein α is the mass ratio of the first particle size material to the second particle size material, and α≥1.
[0060] In some embodiments, 3≤α≤9.
[0061] In some embodiments, α can be 1, 2, 3, 4, 5, 6, 7, 8, 9, or a value in a range consisting of any two of the above points.
[0062] The masses of the first particle size material and the second particle size material can be measured using methods and equipment known in the art. For example, the negative electrode active material is sieved through a sieve to obtain the first particle size material and the second particle size material, and then the masses of the first particle size material and the second particle size material are obtained by weighing.
[0063] Increasing the mass content of silicon-carbon composite materials can improve the mass energy density of secondary batteries. However, excessive amounts of large silicon-carbon composite materials can reduce the compaction density of the negative electrode film layer, decrease the contact area between particles, increase the resistance of the negative electrode sheet, and reduce the rate performance of the secondary battery. The applicant unexpectedly discovered that when the average particle size and mass gradation design relationship of the first and second particle size materials in the negative electrode active material satisfies the above relationship, the secondary battery achieves both high compaction density and high mass energy density, thereby achieving higher volumetric energy density, lower resistance, and higher rate performance.
[0064] In some embodiments, 5 μm≤D1≤20 μm, optionally 5 μm≤D1≤15 μm.
[0065] In some embodiments, D1 may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 18 μm, 20 μm, or a value in a range consisting of any two of the foregoing values.
[0066] When the particle size of the first particle size material is too large, the resistance to charge transfer increases, the rate performance decreases, and the compaction density is also affected. When the particle size of the first particle size material is too small, the silicon-based material contained in the silicon-carbon composite material decreases, thereby reducing the mass energy density of the secondary battery and also reducing the compaction density. Controlling the particle size of the first particle size material within an appropriate range is conducive to increasing the compaction density, reducing the resistance, and improving the rate performance of the secondary battery. It can also increase the mass energy density of the secondary battery.
[0067] In some embodiments, D2 satisfies 1 μm≤D2≤10 μm, and may optionally be 2 μm≤D2≤5 μm.
[0068] In some embodiments, D2 satisfies 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a value in a range consisting of any two of the above points.
[0069] When the particle size of the second particle material is too large, the charge transfer resistance increases, the rate performance decreases, and the compaction density is also affected. When the particle size of the second particle material is too small, the initial efficiency and capacity are low. Controlling the particle size of the second particle material within an appropriate range helps to increase the compaction density, reduce the resistance, and improve the rate performance of the secondary battery. It can also increase the mass energy density of the secondary battery.
[0070] In some embodiments, the particle size distribution of the negative electrode active material satisfies: 0.9≤(Dv90-Dv10) / Dv50≤2.
[0071] In some embodiments, the particle size distribution of the negative electrode active material (Dv90-Dv10) / Dv50 may be 0.9, 1, 1.2, 1.4, 1.6, 1.7, 1.8, 1.9, 2, or a value in a range consisting of any two of the foregoing points.
[0072] In some embodiments, the particle size distribution of the first particle size material satisfies: (Dv190-Dv110) / Dv150≤2.0, which can be optionally 1.2≤(Dv190-Dv110) / Dv150≤2.0; and / or, the particle size distribution of the second particle size material satisfies: (Dv290-Dv210) / Dv250≤1.6, which can be optionally 0.9≤(Dv290-Dv210) / Dv250≤1.3.
[0073] In some embodiments, the particle size distribution (Dv190-Dv110) / Dv150 of the first particle size material can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, or a value within a range consisting of any two of the foregoing points. The particle size distribution (Dv290-Dv210) / Dv250 of the second particle size material can be 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, or a value within a range consisting of any two of the foregoing points.
[0074] Dv90, Dv50 and Dv10 can be measured using methods and equipment known in the art. As an example, the following steps can be referred to: The negative electrode active material is subjected to laser particle size distribution characterization, which can be measured using a laser particle size analyzer (Malvern Master Size 3000) with reference to the standard GB / T 19077.1-2016. The negative electrode active material is sieved through a sieve to obtain a first particle size material and a second particle size material respectively. The obtained first particle size material and the second particle size material are subjected to laser particle size distribution characterization, which can be measured using a laser particle size analyzer (Malvern Master Size 3000) with reference to the standard GB / T 19077.1-2016.
[0075] When the particle size distribution of the negative electrode active material meets the above range, the overall particle size of the negative electrode active material is relatively moderate and the particle size distribution is uniform, which is beneficial to improving the uniformity of the overall performance of the negative electrode active material.
[0076] In some embodiments, the average aspect ratio R1 of the first particle size material is 1.2-2.5; and / or the average aspect ratio R2 of the second particle size material is 1.2-3.0.
[0077] In some embodiments, the average aspect ratio R1 of the first particle size material can be 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 2.0, 2.2, 2.4, or a range consisting of any two of the foregoing values. The average aspect ratio R2 of the second particle size material can be 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, or a range consisting of any two of the foregoing values.
[0078] The average aspect ratio of the first particle size material or the second particle size material can be measured using methods and equipment known in the art, for example, it can be measured using a scanning electron microscope (SEM). As an example, the following steps can be used: an SEM photograph containing a certain amount of first particle size material is obtained by scanning electron microscope. Image J software is used to measure the long diameter and wide diameter of each first particle size material particle, and the ratio of the long diameter to the wide diameter of each first particle size material particle is calculated. The ratio of multiple first particle size material particles in the picture is averaged to obtain R1. Wherein, "wide diameter" refers to the shortest distance passing through the center point of the projected image of the negative electrode active material particle and intersecting with the edge of the projected image. "Long diameter" refers to the longest distance passing through the center point of the projected image of the negative electrode active material particle and intersecting with the edge of the projected image. R2 is obtained in a similar manner to R1. The average aspect ratio of the second particle size material is measured in a similar manner to that of the first particle size material. When R1 and R2 are large, it means that the first and second particle size materials of the negative electrode active material are elongated. The closer R1 and R2 are to 1, the more the first and second particle size materials tend to be ideally spherical.
[0079] By controlling the average aspect ratio of the first particle size material and / or the second particle size material within a suitable range, the particle shapes of the first particle size material and the second particle size material can be controlled to be more regular, thereby increasing the compaction density of the negative electrode film layer.
[0080] In some embodiments, the carbon matrix particles include a three-dimensional network cross-linked pore structure, and at least a portion of the silicon-based material is disposed in the three-dimensional network cross-linked pore structure.
[0081] In the present application, the “three-dimensional network cross-linked pore structure” refers to a structure in which two or more pores are interconnected or interlaced and share pore volume in the pore structure formed by carbon matrix particles.
[0082] The three-dimensional network cross-linked pore structure can provide more space for silicon-based materials, can accommodate more silicon-based materials, and improve the mass energy density of secondary batteries.
[0083] In some embodiments, the carbon content in the silicon-carbon composite material tends to decrease from the geometric center of the silicon-carbon composite material toward the outer surface; and / or, the silicon content in the silicon-carbon composite material tends to increase from the geometric center of the silicon-carbon composite material toward the outer surface.
[0084] In some embodiments, based on the total mass of the silicon-carbon composite material, the silicon content is greater than or equal to 20%, and can be optionally 20%-60%; and / or, based on the total mass of the silicon-carbon composite material, the carbon content is greater than or equal to 40%, and can be optionally 40%-70%; based on the total mass of the silicon-carbon composite material, the oxygen content is less than or equal to 10%, and can be optionally 1%-5%.
[0085] In some embodiments, based on the total mass of the silicon-carbon composite material, the silicon content can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or a value in the range consisting of any two of the above points; and / or, based on the total mass of the silicon-carbon composite material, the carbon content can be 40%, 45%, 50%, 55%, 60%, 65%, 70% or a value in the range consisting of any two of the above points; based on the total mass of the silicon-carbon composite material, the oxygen content can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a value in the range consisting of any two of the above points.
[0086] The content of silicon in the silicon-carbon composite material can be measured using methods and equipment known in the art, for example, it can be measured using emission spectroscopy testing (Inductively coupled plasma, ICP). As an example, the following steps can be used: take a silicon-carbon composite material as a sample, digest the sample with a strong acidic solution (such as aqua regia and hydrofluoric acid HF), and the silicon content in the solution at different digestion times is the silicon content distributed from the geometric center to the outer surface or from the outer surface to the geometric center. The silicon content in the completely digested solution is the average content of silicon based on the total mass of the silicon-carbon composite material.
[0087] The carbon content in the silicon-carbon composite material can be measured using methods and equipment known in the art, such as infrared absorption carbon-sulfur content analysis, according to the GB / T20123-2006 test standard. As an example, the following steps can be used: A carbon-silicon composite material is taken as a sample, and the carbon content at different times is measured as the carbon content distributed from the geometric center to the outer surface, or from the outer surface to the geometric center. The carbon content at the end of the test is the average carbon content based on the total mass of the silicon-carbon composite material.
[0088] When the content of the silicon-based material attached to the interior of the carbon-based particles of the present application meets the above range, the relatively high content of the silicon-based material can significantly increase the capacity of the secondary battery, thereby increasing its mass energy density. A moderate content of the carbon-based particles can improve the conductivity of the negative electrode active material, thereby reducing the resistance of the negative electrode sheet.
[0089] In some embodiments, the mass content of the silicon-carbon composite material in the negative electrode active material is greater than or equal to 50%, and can be optionally greater than or equal to 70%.
[0090] In some embodiments, the mass content of the silicon-carbon composite material in the negative electrode active material may be 50%, 60%, 70%, 75%, 80%, 85%, 90%, or a value within a range formed by any two of the above points.
[0091] When the content of silicon-carbon composite material increases, it is beneficial to improve the mass energy density of the secondary battery.
[0092] In some embodiments, the second particle size material comprises a carbon-based material; optionally, the carbon-based material comprises one or more of graphite, hard carbon, soft carbon, porous carbon, or activated carbon.
[0093] In some embodiments, the second particle size material may further include one or more of a silicon-carbon material or a silicon-oxygen material.
[0094] In some embodiments, the silicon-carbon material includes a silicon-coated carbon material, a carbon-coated silicon material, a silicon-carbon material having a carbon skeleton, or a mixed material containing silicon particles and carbon particles.
[0095] When the second particle size material includes a carbon-based material, the ability of the negative electrode plate to transport ions can be improved, and the rate performance of the secondary battery is effectively improved.
[0096] In some embodiments, the negative electrode sheet includes a negative electrode film layer having a compaction density of 1.2 g / cm 3 -1.6g / cm 3 Optionally, the compaction density of the negative electrode film is 1.3 g / cm 3 -1.6g / cm 3 .
[0097] In some embodiments, the compaction density of the negative electrode film layer can be 1.2 g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm3 Or a value within the range formed by the above two points.
[0098] The compacted density of the negative electrode film layer can be measured by methods and equipment known in the art. As an example, the compacted density of the negative electrode film layer can be measured by referring to the following steps: compacted density of the negative electrode film layer = m / (V1-V2), where m represents the weight of the negative electrode film layer, V1 represents the volume of the electrode, and V2 represents the volume of the current collector. m can be obtained by subtracting the weight of the current collector from the weight of the electrode. The product of the surface area of the electrode and the thickness of the electrode is the volume V1 of the electrode. The product of the surface area of the electrode and the thickness of the current collector is V2. The thickness of the current collector and the thickness of the electrode are obtained by measuring the thickness of the empty foil in the tab area with a micrometer.
[0099] When the compaction density of the negative electrode film layer is increased, the volume energy density of the secondary battery can be significantly improved.
[0100] In some embodiments, the negative electrode sheet further includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, and the negative electrode film layer includes the negative electrode active material of the present application.
[0101] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0102] In some embodiments, the thickness of the negative electrode current collector may be 6-20 μm, alternatively, 6-10 μm. In some embodiments, the thickness of the negative electrode current collector may be 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, or a value in a range consisting of any two of the above points.
[0103] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0104] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0105] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0106] [Positive electrode]
[0107] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0108] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is provided on either or both of the two facing surfaces of the positive electrode current collector.
[0109] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0110] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0111] In some embodiments, the positive electrode active material may include Li a Ni b Co c M d O e A f At least one of lithium transition metal oxides and modified compounds thereof, wherein 0<a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 0<e≤2, 0≤f≤1, M includes at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A includes at least one of N, F, S and Cl.
[0112] The modified compound may be a compound obtained by doping and / or coating a lithium transition metal oxide.
[0113] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0114] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0115] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0116] [Electrolytes]
[0117] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0118] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0119] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0120] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0121] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0122] [Isolation film]
[0123] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0124] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0125] [Secondary Battery Preparation Method]
[0126] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0127] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0128] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG2 shows a secondary battery 5 having a square structure as an example.
[0129] In some embodiments, referring to FIG3 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0130] In some embodiments, the mass energy density of the secondary battery is 380Wh / kg-460Wh / kg, optionally, the mass energy density of the secondary battery is 400Wh / kg-460Wh / kg; and / or the volume energy density of the secondary battery is 650Wh / L-1000Wh / L, optionally, the volume energy density of the secondary battery is 700Wh / L-1000Wh / L.
[0131] The mass energy density and volume energy density of a secondary battery can be measured using methods and equipment commonly used in the art. As an example, the mass energy density of a secondary battery can be measured using the following steps: Place the secondary battery on an electronic balance until the weight stabilizes, and read the secondary battery weight value M0. After charging the secondary battery to a charge cutoff voltage (e.g., 4.25V) at a certain temperature (e.g., 25°C) and a certain rate (e.g., 0.33C), continue constant voltage charging at the charge cutoff voltage until the current reaches 0.05C, and the charge is cutoff (C represents the rated capacity of the secondary battery). At a certain temperature (e.g., 25°C) and a certain rate (0.33C), discharge the secondary battery to a discharge cutoff voltage (e.g., 2.0V), record the discharge capacity C0 released by the secondary battery, and the total discharge energy is E0. Secondary battery mass energy density = secondary battery discharge energy E0 / secondary battery weight M0. As an example, the volume area energy of a secondary battery can be measured using the following steps: Use a ruler to measure the length, width, and height of the secondary battery to obtain the volume value V0 of the secondary battery. The total discharge capacity E0 of the secondary battery is measured. Secondary battery volume energy density = secondary battery discharge energy E0 / secondary battery volume V0.
[0132] In some embodiments, the mass energy density of the secondary battery can be 380Wh / kg, 390Wh / kg, 400Wh / kg, 410Wh / kg, 420Wh / kg, 430Wh / kg, 440Wh / kg, 450Wh / kg, 460Wh / kg, or a value in a range consisting of any two of the foregoing points. In some embodiments, the volumetric energy density of the secondary battery can be 650Wh / L, 700Wh / L, 800Wh / L, 900Wh / L, 950Wh / L, 1000Wh / L, or a value in a range consisting of any two of the foregoing points.
[0133] [Battery Module]
[0134] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0135] Figure 4 shows an example battery module 4. Referring to Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0136] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0137] [Battery Pack]
[0138] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0139] Figures 5 and 6 illustrate an example battery pack 1. Referring to Figures 5 and 6 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0140] [Electrical devices]
[0141] A second aspect of the present application provides an electrical device, which includes the secondary battery of the present application.
[0142] Electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.
[0143] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0144] [Corrected 17 May 2023 in accordance with Rule 91] [Corrected 17 May 2023 in accordance with Rule 91] Figure 7 shows an example of an electric device. This device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of secondary batteries, a battery pack or battery module can be used.
[0145] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0146] Example
[0147] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0148] Example 1
[0149] 1. Preparation method
[0150] 1. Preparation of positive electrode sheet
[0151] The positive electrode active material lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 O2, binder polyvinylidene fluoride (PVDF), and conductive agent conductive carbon black (Super P) are evenly mixed in N-methylpyrrolidone (NMP) solvent in a mass ratio of 96%:2%:2% to prepare a positive electrode slurry. The positive electrode slurry is coated on the surface of aluminum foil and dried, and then cold pressed to prepare a positive electrode sheet.
[0152] 2. Preparation of negative electrode sheet
[0153] Preparation of silicon-carbon composite materials: Carbon matrix particles with a three-dimensional network cross-linked pore structure are prepared by a template method, specifically using SiO2 molecular sieve as a template agent and sucrose as a carbon source, and obtaining carbon matrix particles after removing the template through liquid phase mixing, drying, high-temperature carbonization, and acid treatment; Silane is used as a silicon precursor, and the silicon precursor is attached to the three-dimensional network cross-linked pore structure by chemical vapor deposition to obtain a silicon-carbon composite material. The average particle size D1 of the obtained silicon-carbon composite material is 14 μm, the average aspect ratio R1 is 1.5, and the particle size distribution (Dv190-Dv110) / Dv150 is 1.8.
[0154] A first particle size silicon-carbon composite material and a second particle size artificial graphite (the mass ratio of the two is 90%:10%, i.e., α=9), a conductive agent carbon black, a binder styrene-butadiene rubber (SBR), and a thickener sodium carboxymethyl cellulose (CMC) are thoroughly stirred and mixed in an appropriate amount of deionized water in a mass ratio of 93.5%:1.8%:3.5%:1.2% to form a uniform negative electrode slurry. The negative electrode slurry is applied to a negative electrode current collector and dried to obtain a negative electrode. The artificial graphite has an average particle size D2 of 3.5 μm, an average aspect ratio R2 of 1.3, and a particle size distribution (Dv290-Dv210) / Dv250 of 1.2.
[0155] 3. Isolation film
[0156] Polyethylene film (PE) is used as the isolation film.
[0157] 4. Electrolyte
[0158] Ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0159] 5. Battery preparation
[0160] The positive electrode sheet, separator, and negative electrode sheet are sequentially wound or stacked to form an electrode assembly. The electrode assembly is placed in a packaging shell, dried, and then injected with electrolyte. The lithium-ion secondary battery is obtained through vacuum packaging, static standing, formation, and shaping. Specific parameters are shown in Table 1.
[0161] Example 2-Example 18
[0162] The preparation method is similar to that of Example 1, except that the relevant parameters of the first particle size material and the second particle size material are adjusted or the type of the second particle size material is adjusted to obtain the corresponding secondary battery. Specific parameters are shown in Table 1.
[0163] Comparative Example 1
[0164] The preparation method is similar to that of Example 1, except that the average particle sizes of the first particle size material and the second particle size material are adjusted to obtain the corresponding secondary battery. Specific parameters are shown in Table 1.
[0165] 2. Performance Testing
[0166] 1. Battery performance test
[0167] 1.1 Mass energy density and volume energy density test
[0168] 1) The discharge energy measurement method of secondary batteries is as follows:
[0169] Place the secondary battery on an electronic balance until the weight stabilizes, and read the secondary battery weight value M0.
[0170] Use a ruler to measure the length, width, and height of the secondary battery, and calculate the volume value V0 of the secondary battery.
[0171] After the secondary battery is charged at 0.33C to a charge cutoff voltage of 4.25V at 25°C, constant voltage charging is continued at the charge cutoff voltage until the current reaches 0.05C, and charging is terminated (where C represents the rated capacity of the secondary battery).
[0172] The secondary battery was discharged at 0.33C at 25°C to a discharge cut-off voltage of 2.0V, and the total discharge capacity C0 released by the secondary battery was recorded, and the total discharge energy E0.
[0173] Secondary battery mass energy density = secondary battery discharge energy E0 / secondary battery weight M0.
[0174] Secondary battery volume energy density = secondary battery discharge energy E0 / secondary battery volume V0.
[0175] 1.2. Rate performance
[0176] At 25°C, fully charge the battery at 0.33C and fully discharge it at 1C 10 times, then fully charge the battery at 2C. Remove the negative electrode and observe the lithium deposition on the surface of the negative electrode. If no lithium deposition occurs on the negative electrode surface, increase the charge rate by 0.1C in increments of 2C until lithium deposition occurs on the negative electrode surface. Stop the test and subtract 0.1C from the charge rate at this point to obtain the maximum charge rate of the battery.
[0177] 3. Analysis of test results of various embodiments and comparative examples
[0178] Batteries of various embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The parameters of the negative electrode sheets are shown in Table 1 below, and the performance test results of the negative electrode sheets and secondary batteries are shown in Table 2 below.
[0179] Table 2 Negative electrode and secondary battery performance test results
[0180] According to the results in the above table, it can be seen from Comparative Example 1 and Examples 1-18 that by adding a second particle size material to the negative electrode active material and limiting the average particle size relationship between the first particle size material and the second particle size material to be within the scope of the present application, the compaction density of the negative electrode film layer can be increased, the resistance can be reduced, and the mass energy density of the secondary battery can be increased, thereby further improving the volume energy density and rate performance of the secondary battery.
[0181] It can be seen from Examples 1-4 that by further limiting the relationship between the average particle size and mass of the first particle size material and the second particle size material, the secondary battery is beneficial to having both high compaction density and high mass energy density, thereby having a higher volume energy density, while also having lower resistance and higher rate performance.
[0182] As can be seen from Examples 1 and 5-8, limiting the average particle size of the first particle size material and the second particle size material to the range of this application is beneficial to increasing the compaction density, reducing the resistance, and improving the rate performance of the secondary battery. It can also increase the mass energy density of the secondary battery.
[0183] It can be seen from Examples 9-12 that limiting the aspect ratio of the first particle size material to the second particle size material within the scope of the present application is beneficial to improving the compaction density of the film layer.
[0184] It can be seen from Example 1 and Examples 13-16 that limiting the particle size distribution of the negative electrode active material, the first particle size material, and the second particle size material to within the scope of the present application is beneficial to improving the compaction density of the negative electrode film layer.
[0185] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode active material, wherein the negative electrode active material comprises a first particle size material and a second particle size material, wherein an average particle size D1 of the first particle size material and an average particle size D2 of the second particle size material satisfy: D2 / D1≤0.6, and the first particle size material comprises a silicon-carbon composite material, wherein the silicon-carbon composite material comprises carbon matrix particles and a silicon-based material disposed inside the carbon matrix particles.
2. The secondary battery according to claim 1, characterized in that: D2 / D1≤0.6-0.155lnα, wherein α is the mass ratio of the first particle size material to the second particle size material, and α≥1.
3. The secondary battery according to claim 2, characterized in that: 3≤α≤9。 4. The secondary battery according to any one of claims 1 to 3, characterized in that: 5μm≤D1≤20μm, optionally 5μm≤D1≤15μm.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: 1μm≤D2≤10μm, optionally 2μm≤D2≤5μm.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The particle size distribution of the negative electrode active material satisfies: 0.9≤(Dv90-Dv10) / Dv50≤2.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: The particle size distribution of the first particle size material satisfies: (Dv190-Dv110) / Dv150≤2.0, which can be optionally 1.2≤(Dv190-Dv110) / Dv150≤2.0; and / or, the particle size distribution of the second particle size material satisfies: (Dv290-Dv210) / Dv250≤1.6, which can be optionally 0.9≤(Dv290-Dv210) / Dv250≤1.
3.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The average aspect ratio R1 of the first particle size material is 1.2-2.5; and / or the average aspect ratio R2 of the second particle size material is 1.2-3.
0.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The carbon matrix particles include a three-dimensional network cross-linked pore structure, and at least a portion of the silicon-based material is disposed in the three-dimensional network cross-linked pore structure.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The carbon content in the silicon-carbon composite material tends to decrease from the geometric center of the silicon-carbon composite material to the outer surface; and / or the silicon content in the silicon-carbon composite material tends to increase from the geometric center of the silicon-carbon composite material to the outer surface.
11. The secondary battery according to claim 10, characterized in that: Based on the total mass of the silicon-carbon composite material, the silicon content is greater than or equal to 20%, and can be optionally 20%-60%; and / or, Based on the total mass of the silicon-carbon composite material, the carbon content is greater than or equal to 40%, and can be optionally 40%-70%; Based on the total mass of the silicon-carbon composite material, the content of oxygen is less than or equal to 10%, and can be optionally 1%-5%.
12. The secondary battery according to any one of claims 1 to 11, characterized in that: The mass content of the silicon-carbon composite material in the negative electrode active material is greater than or equal to 50%, and can be optionally greater than or equal to 70%.
13. The secondary battery according to any one of claims 1 to 12, characterized in that: The second particle size material includes a carbon-based material; optionally, the carbon-based material includes one or more of graphite, hard carbon, soft carbon, porous carbon or activated carbon.
14. The secondary battery according to any one of claims 1 to 13, wherein the negative electrode sheet comprises a negative electrode film layer, characterized in that: The compaction density of the negative electrode film layer is 1.2 g / cm 3 -1.6g / cm 3 Optionally, the compaction density of the negative electrode film layer is 1.3 g / cm 3 -1.6g / cm 3 .
15. The secondary battery according to any one of claims 1 to 14, characterized in that: The mass energy density of the secondary battery is 380Wh / kg-460Wh / kg, optionally, the mass energy density of the secondary battery is 400Wh / kg-460Wh / kg; and / or, the volume energy density of the secondary battery is 650Wh / L-1000Wh / L, optionally, the volume energy density of the secondary battery is 700Wh / L-1000Wh / L.
16. An electrical device comprising the secondary battery according to any one of claims 1 to 15.
Citation Information
Cited By
Negative pole piece, solid-state battery and electric device
CN120709351A